Museological mediation and the challenges of inclusion: a study on the Museum of Sacred Art Writer Maximiano Campos - Castro, Eva Caroline de Sena (Revista do Colóquio, 2023)
This research aims to analyze the effectiveness of educational actions in museological spaces that promote the promotion of an interaction and a dialogue between the visiting public and as works of art. Taking as a starting point the triangular relationship between public-mediator-work of art, the importance of this interaction and how it is legitimized was understood. Based on a specific analysis of the collection of the Museu de Arte Sacra Escritor Maximiano Campos, located in the city of Goiana - PE, from the experience with mediation in this place, and considering the audience it reaches, an educational and inclusive activity is required for specific audiences. Considering, above all, to an action that can cover subjects from the most varied social spheres, about socioeconomic nature, as well as age diversity.